2012
DOI: 10.1016/j.colsurfa.2011.12.057
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation in mixed monolayers of arachidic acid and a phthalocyanine of zinc

Abstract: Mixed Langmuir and Langmuir-Blodgett films of dissimilar components, arachidic acid and a phthalocyanine of zinc, have been investigated. These compounds form mixed films with phase separation, with domains at the sub-micro scale which are detected by AFM in LB films but not observed by BAM. These domains present different contrast in the surface potential images obtained with SP-AFM and in the friction images. The analysis of the isotherms and of the AFM images, at several compositions, reveals that the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…40,41 ). The effects of solutes on lipid organization can be assessed in terms of the changes in the area per lipid molecule, phase transition pressures and inverse compressibility modulus values 34,[42][43][44] . These can be directly related to the properties of bilayers: for example, the gel and fluid phases of a bilayer are analogous to the liquid condensed and liquid expanded phases, respectively, of a monolayer 35,[45][46][47] .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…40,41 ). The effects of solutes on lipid organization can be assessed in terms of the changes in the area per lipid molecule, phase transition pressures and inverse compressibility modulus values 34,[42][43][44] . These can be directly related to the properties of bilayers: for example, the gel and fluid phases of a bilayer are analogous to the liquid condensed and liquid expanded phases, respectively, of a monolayer 35,[45][46][47] .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…However, it also seems that the reorganization of GTO and Pyro-A molecules participate in the smoothing of the monolayer. Torrent-Burgués observed that a fatty acid mixed with a phthalocyanine contributes to the formation of a more uniform phase despite the phase separation between the two immiscible compounds.…”
Section: Resultsmentioning
confidence: 99%
“…However, BAM images show that after a few compression cycles, the morphology of monolayers containing high Pyro-A molar fraction appears more uniform. Torrent-Burgués observed a decrease in the compactness of a phthalocyanine monolayer when mixed with a fatty acid due to the insertion of fatty acid chains between the photosensitizer molecules. Thus, the organization of densely packed Pyro-A molecules after partial collapse of GTO molecules might still be impacted by the triglyceride.…”
Section: Resultsmentioning
confidence: 99%